Oral complications of diabetes mellitus and their underlying pathogenic mechanisms: a narrative review - Hamad Alfarisi, Hamad Abdulsalam; Dowlath Saheb, Samiullah (IIUM Press, 2026)
Diabetes mellitus (DM) is a syndrome of abnormal carbohydrate metabolism causing tremendous mortality and morbidly worldwide. To date, there is no permanent curative treatment for diabetes and the patients have to rely on modification of their lifestyle and on the available timely medication. Understanding pathophysiology and complications of DM is crucial for clinicians and dental care providers in order to provide a proper management. Complications of DM are multisystemic with inevitable involvement of oral cavity. Diabetic patients have increased frequency of periodontitis, xerostomia, tooth loss, delay in wound healing, and impaired response to infection. Dental complications of DM exert medical, psychological, economical and national burden. This narrative review aims to outline the oral complications of DM and their underlying pathogenic mechanisms in the recent literature. The review concluded that; the commonest oral complications of DM are xerostomia, tooth decay, periodontal disease and gingivitis, oral candidiasis, altered taste sensation, oral mucosa alterations, and delayed wound healing. The important underlying pathogenic mechanisms include oxidative stress, alterations in salivary amylase protein, high level of sodium-glucose cotransporter 1 (SGLT1) protein, impaired neural structure and function, use of sodium glucose transporter 2 (SGLT2) inhibitor, the influence of the IL-23R gene polymorphism, and formation of advanced glycation end products (AGEP)